2016
DOI: 10.1136/jclinpath-2015-203211
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal malignant mesothelioma (PMM), and primary peritoneal serous carcinoma (PPSC) and reactive mesothelial hyperplasia (RMH) of the peritoneum. Immunohistochemical and fluorescence in situ hybridisation (FISH) analyses

Abstract: Calretinin and BerEP4 may be the best positive markers for differentiating PMM from PPSC. EMA, in combination with IMP3 and desmin, is useful, and homozygous deletion of 9p21 may be helpful, for differentiating PMM from RMH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 36 publications
3
37
0
Order By: Relevance
“…Mesothelioma is a rare primary tumour of the female genital tract, most commonly with a benign natural history though potential for benign recurrence locally ( Horn and Leqis, 1951 ). This tumour was favoured to represent mesothelioma due to combined presence of calretinin, CK 5/6, D2 40, WT 1 and PAX 8, as PAX8 has been previously observed by mesothelioma experts in intra-peritoneal lesions ( Kawai et al, 2016 , Laury et al, 2010 ). Ovarian papillary serous and clear-cell tumour are documented to show stronger PAX8 activity though the absence of BerEP4, mCEA, oestrogen receptor, progestogen receptor and desmin make these tumours less likely in this case.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Mesothelioma is a rare primary tumour of the female genital tract, most commonly with a benign natural history though potential for benign recurrence locally ( Horn and Leqis, 1951 ). This tumour was favoured to represent mesothelioma due to combined presence of calretinin, CK 5/6, D2 40, WT 1 and PAX 8, as PAX8 has been previously observed by mesothelioma experts in intra-peritoneal lesions ( Kawai et al, 2016 , Laury et al, 2010 ). Ovarian papillary serous and clear-cell tumour are documented to show stronger PAX8 activity though the absence of BerEP4, mCEA, oestrogen receptor, progestogen receptor and desmin make these tumours less likely in this case.…”
Section: Discussionmentioning
confidence: 61%
“…Patient presented with widespread disease involving fallopian tube Diagnosed at time of planned TAH BSO. Nil evidence of recurrence at 3 years 2 ( Kawai et al, 2016 ) 1961 Mesothelioma of the Salpinx Nil details available 3 ( Laury et al, 2010 ) 2012 Incidental finding during hysterectomy for leiomyoma Chronic xanthogranuloma-tous salpingiosis Planned hysterectomy. Nil further treatment …”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32] Some propose that M€ ullerian metaplasia of the peritoneum is the source of endometriosis, due to expression of BerEP4, ER and PR in mesothelial cells of the ovary and peritoneum. 33 As mentioned previously, mesotheliomas and benign mesothelium reportedly express M€ ullerian markers such as PAX8, PAX2, ER and PR, 23,27,[34][35][36] suggesting a dynamic balance between mesothelial and M€ ullerian cells in the peritoneum. 21 We used digital microscopy and computer analysis to determine the cell count in ovarian CICs and found that, contrary to previous reports, metaplasia occurs in entrapped OSE, from PAX8 À /calretinin + mesothelial cells to PAX8 + /calretinin À FT-like cells; these could account for the proportion of HGSCs that arise in the ovary without an associated fallopian tube neoplasm.…”
Section: Examples In Other Organ Systems Include Intestinal Metaplasimentioning
confidence: 60%
“…Some propose that Müllerian metaplasia of the peritoneum is the source of endometriosis, due to expression of BerEP4, ER and PR in mesothelial cells of the ovary and peritoneum . As mentioned previously, mesotheliomas and benign mesothelium reportedly express Müllerian markers such as PAX8, PAX2, ER and PR, suggesting a dynamic balance between mesothelial and Müllerian cells in the peritoneum …”
Section: Discussionmentioning
confidence: 72%
“…The increase in excised graft thickness was exclusively a result of an increase in the dermal thickness, with no significant change in the thickness of the epidermis, and no evidence of residual Vicryl mesh ( Figure 6 and Figure 7). To further characterize the morphology of the interface between visceral skin graft and peritoneal cavity, calretinin and WT-1 immunostaining was utilized to identify and localize mesothelial cells [18]. Colocalization of calretinin and WT-1 immunoreactivity confirmed the presence of mesothelial cells throughout the dermal matrix of the excised skin grafts, primarily in perivascular locations ( Figure 10).…”
Section: Graft Histopathologymentioning
confidence: 99%